2020
DOI: 10.1103/physrevlett.125.202701
|View full text |Cite
|
Sign up to set email alerts
|

First Direct Measurement of Mg22(α,p)Al

Abstract: Type-I x-ray bursts can reveal the properties of an accreting neutron star system when compared with astrophysics model calculations. However, model results are sensitive to a handful of uncertain nuclear reaction rates, such as 22 Mgðα;pÞ. We report the first direct measurement of 22 Mgðα;pÞ, performed with the Active Target Time Projection Chamber. The corresponding astrophysical reaction rate is orders of magnitude larger than determined from a previous indirect measurement in a broad temperature range. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…Finally, we note that if we assume that the E x = 8.985(8)-MeV state and the broad E x = 9.029(7)-keV state are the same state, the present data support a stronger p 1 decay branch for this state compared to the p 0 branch. In this case, proton peaks at E x = 3152 (8) keV or E p = 3186 (7) keV (depending on the choice of energy for the initial state) should be observed in the βp decay of 22 Al, which is not the case. This is another inconsistency between the presently observed branching ratios and the 22 Al βp decay data.…”
Section: B States At Ex ∼ 9 Mevmentioning
confidence: 97%
See 4 more Smart Citations
“…Finally, we note that if we assume that the E x = 8.985(8)-MeV state and the broad E x = 9.029(7)-keV state are the same state, the present data support a stronger p 1 decay branch for this state compared to the p 0 branch. In this case, proton peaks at E x = 3152 (8) keV or E p = 3186 (7) keV (depending on the choice of energy for the initial state) should be observed in the βp decay of 22 Al, which is not the case. This is another inconsistency between the presently observed branching ratios and the 22 Al βp decay data.…”
Section: B States At Ex ∼ 9 Mevmentioning
confidence: 97%
“…Unfortunately, there is some disagreement about the properties of levels at E x ∼ 9 MeV. The ENSDF database [41] gives E x = 8991 (7) keV for a state with a tentative J π = 1 − assignment. The J π = 1 − assignment comes from the 21 Na(p, p) 21 Na resonance scattering experiments of He et al and Zhang et al [26,27] in which a state is observed at E x = 9.050 (30) MeV.…”
Section: B States At Ex ∼ 9 Mevmentioning
confidence: 99%
See 3 more Smart Citations